Best Proximity Point Theorems for Multi-Valued Mappings in Complete Metric Spaces - Yadav, M.R.; Thakur, B.S.; Sharma, A.K (Sarajevo Journal of Mathematics, 2024)
In this paper the concept of K-cyclic and C-cyclic contraction single-valued maps are extended to multi-valued maps with MT-functions in the frameworks of complete spaces. We show the existence of a best proximity point for such mappings in the setup of complete metric spaces. Our result extends and improves some best proximity point theorems in the literature. An example is given to support the functionality of the result. 2010 Mathematics Subject Classification. 41A65, 46B20, 47H10, 46J10, 46J15.